2009
DOI: 10.1002/pd.2413
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal exclusion of haemoglobin Bart's using foetal DNA from maternal plasma

Abstract: We show proof-of-principle that such a test can accurately exclude HbBart's in the foetus by identifying the nondeleted paternally inherited fetal alleles in maternal plasma in one out of three pregnancies, avoiding invasive testing in these pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Our results showed that indirect testing based on fluorescent multiplex PCR can be safely used for NIPD, reaching sensitivity and specificity similar to those seen in previous studies [10,21,23,24]. However, this test is less informative than the SNP-haplotype-based approach by next-generation sequencing [25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our results showed that indirect testing based on fluorescent multiplex PCR can be safely used for NIPD, reaching sensitivity and specificity similar to those seen in previous studies [10,21,23,24]. However, this test is less informative than the SNP-haplotype-based approach by next-generation sequencing [25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 67%
“…Each peak in the stutter lacks one core repeat unit relative to the main peak. When the paternal amplicon size is directly adjacent to the maternal amplicon size, it may be very difficult to distinguish the signals [18,21,22]. The feasibility of using this NIPD protocol for each couple depends on the availability of family members (of offspring or relative gDNA) for determining the haplotypes linked to mutant or normal alleles in the family.…”
Section: Discussionmentioning
confidence: 99%
“…One investigation failed to reliably diagnose Hemoglobin Bart's using real-time quantitative PCR [112]. Another investigation utilized qualitative fluorescence PCR to exclude Hemoglobin Bart's in 10/30 pregnancies, via detection of nondeleted paternally inherited fetal alleles [113]. …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Recent studies have reported non-invasive prenatal diagnosis (NIPD) by genetic analysis of free fetal DNA isolated from maternal plasma 24 25. This avoids the increased risk of miscarriage26 associated with conventional invasive prenatal testing but, without NGS, the application is largely limited to screening for specific variants inherited from the father or arising de novo in the fetus, as discrimination of fetal and maternal alleles and aneuploidy detection are extremely challenging.…”
Section: Diagnosismentioning
confidence: 99%